2021
DOI: 10.1021/acsomega.1c02162
|View full text |Cite
|
Sign up to set email alerts
|

Low pH-Based Method to Increase the Yield of Plant-Derived Nanoparticles from Fresh Ginger Rhizomes

Abstract: Plant-derived nanoparticles (PDNPs) are naturally occurring exosome-like nanovesicles derived from dietary plants containing key plant bioactives. Ginger-derived PDNPs have a therapeutic effect on alcohol-induced liver injury, inflammatory bowel disease, and colon cancer. PDNPs are conventionally purified by differential ultracentrifugation, a technique not amenable for scale up. We have recently developed a polyethylene glycol (PEG) 6000-based method for cost-effective purification of ginger PDNPs, with compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…37 Others extracted GELNs using PEG6000 based on the principle of polymer precipitation. 38 However, there is still a lack of available extraction methods at present. In this work, we attempted to extract GELNs by differential centrifugation combined with the commercial kit, and the feasibility of this method was confirmed via characterization of GELNs by TEM and dynamic light scattering (DLS).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Others extracted GELNs using PEG6000 based on the principle of polymer precipitation. 38 However, there is still a lack of available extraction methods at present. In this work, we attempted to extract GELNs by differential centrifugation combined with the commercial kit, and the feasibility of this method was confirmed via characterization of GELNs by TEM and dynamic light scattering (DLS).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Although some scholars purified the exosome-like nanoparticles from sunflower seeds via selective extraction of apoplastic fluid by vacuum infiltration procedure . Others extracted GELNs using PEG6000 based on the principle of polymer precipitation . However, there is still a lack of available extraction methods at present.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with a previous isolation method of plant-derived exosome-like nanoparticles from carrot, apple, lemon, grape, grapefruits, tea leaves, cabbage, ginger, and garlic [32][33][34][35][36][37][38], we established the double fractionation of GDEs by sucrose-based isolation to purify GDEs from vesicle aggregates or contaminated proteins for reproducible high-quality exosome-like nanoparticles. To collect homogeneously sized GDEs with high yield, we first isolated non-contaminated intact EVs from ginseng juice through sucrose cushion of different densities, which can prevent the degradation of EVs during repeated highforce centrifugations.…”
Section: Discussionmentioning
confidence: 99%
“…PEG methods are related to pH. Suresh et al reported a higher yield of PELNs when PEG precipitation was carried out in pH 4 and 5 (58). PELNs can be internalized in plant cells, mammalian cells, fungi, and bacteria (28,(45)(46)(47).…”
Section: Pelns Biogenesis and Isolationmentioning
confidence: 99%